Improvement of structure and properties of cast ferrite-pearlite steels for transport machine building - Rabinovich, A.V.; Bublikov, Yu.A.; Tregubenko, G.N.; Polyakov, G.A.; Puchikov, A.V.; Dementieva, Zh.A. (Современная электрометаллургия, 2008)
Technology for complex modification of casting from low-alloy ferrite-pearlite steels by titanium, aluminium and nitrogen was developed, which ensures increase of the lower level of yield strength in normalized (³ 380 MPa) and temper hardened (³ 450 MPa) state, the rest requirements to mechanical properties of the 20GL steel being preserved. Разработана технология комплексного модифицирования литья из низколегированных феррито-перлитных сталей титаном, алюминием и азотом, обеспечивающая повышение нижнего уровня предела текучести в нормализованном (> 380 МПа) и закаленном после отпуска (> 450 МПа) состоянии при сохранении остальных требований к механическим свойствам стали 20ГЛ.